2021
DOI: 10.3390/app11136229
|View full text |Cite
|
Sign up to set email alerts
|

Lane Detection Algorithm Using LRF for Autonomous Navigation of Mobile Robot

Abstract: This paper proposes a lane detection algorithm using a laser range finder (LRF) for the autonomous navigation of a mobile robot. There are many technologies for ensuring the safety of vehicles, such as airbags, ABS, and EPS. Further, lane detection is a fundamental requirement for an automobile system that utilizes the external environment information of automobiles. Representative methods of lane recognition are vision-based and LRF-based systems. In the case of a vision-based system, the recognition of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…According to J.H. Han et al [19], a web camera installed on the AGV was used to extract road features, and the AGV successfully traveled, as shown in Figure 21a,b. The test is conducted on a bright and sunny day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to J.H. Han et al [19], a web camera installed on the AGV was used to extract road features, and the AGV successfully traveled, as shown in Figure 21a,b. The test is conducted on a bright and sunny day.…”
Section: Discussionmentioning
confidence: 99%
“…J.H. Han et al [19] used a feature point extraction technique with LRF calibration and amplification errors dependent on the materials and colors of the asphalt and lanes to create a laser-scanned 3D road map and to identify and recognize lanes. The test results revealed that using their method could assure safe driving under poor road conditions, such as fog and curvature paths, which might help in the research and development of autonomous driving technologies.…”
Section: Related Workmentioning
confidence: 99%